Phenotypic Detection of Extended Spectrum Î²-lactamase-producing Bacteria from Selected Hospital Contact Surfaces - Garba, Lawal; Chiroma, Nune M.; Justine, Jessica; Yusuf, I.; Inuwa, A.B.; Idris, Abdulrahman (Journal of Environmental Microbiology and Toxicology, 2020)
Community and hospital acquired infections caused by drug resistant organisms especially the extended spectrum Î²-lactamase producers among members of the family Enterobacteriaceae have been on a global increase. Such infections could lead to an increased healthcare costs, morbidity and mortality. The Extended Spectrum Î²-lactamases are enzymes produced by some bacteria to inactivate group of Î²-lactam antibiotics such as penicillin and its derivatives as well as broad spectrum cephalosporins including monobactams. The enzymes have been the key source of multidrug resistance among many Gram-negative bacteria. Previous studies conducted on Extended Spectrum Î²-lactamase (ESÎ²L) in Gombe Specialist Hospital focused more attention on the occurrence of the ESÎ²L producing bacteria in clinical samples. This study aimed at phenotypic detection of ESÎ²L producing bacteria from some selected contact surfaces in the same hospital for the first time to the best of our knowledge. One hundred and fifty (150) samples were collected from contact surfaces such as door handles, wheelchairs, ATM machines etc. using sterile swab sticks. The samples were cultured on nutrient and MacConkey agar plates to isolate bacterial contaminants. The bacterial isolates were identified using standard procedures. Gram negative isolates were screened for the potential ESÎ²L producers using CLSI breakpoint and phenotypically confirmed using double disc synergy test (DDST). The results obtained confirmed high ESÎ²L producers among E. coli with 20 (44.40%) followed by K. pneumoniae with 15 (33.30%) and then P. mirabilis having the least confirmed isolates. In conclusion, the ESÎ²L producers detected from the contact surfaces suggest the adoption of more personal and environmental hygiene practices to limit the spread of drug resistant organisms and possible outbreak of nosocomial infections.